Popular public entertainment in Iloilo City 1900-1960's. - German, Mary Acel Delgado (1992.)
This descriptive historical study was conducted to examine the various forms of popular public entertainment in Iloilo city during the year 1900-1960's. Library research and personal interviews were conducted in order to: describe the socio-economic conditions of Iloilo City during the year 1900-1960's, to identify the types of popular public entertainment that existed in Iloilo City during the years under study, and to determine the bearing of the socio-economic conditions on certain forms of popular public entertainment., The entertainments during special occasions. entertainments that fell under the category of performing arts were zarzuelas, vaudevilles, movies, concerts, stage plays and radio programs. Billiards, sports, and gambling were classified under the category of games while entertainments during special occasions were in the forms of carnivals, Jaro fiesta celebrations, July four parades and occasional exhibits. Findings revealed that during the boom of the sugar and shipping industries, conditions such as high employment rate, Iloilo becoming the center of trade for the whole Western Visayas and the rise of an atmosphere of social sophistication and the influx of western influence provided a condition in which popular public entertainments sprouted, grew and flowered. During the decline of the two industries, several changes in the socio-economic conditions like loss of employment and the exodus of the sugar traders from Iloilo affected the popularity of some forms of entertainment. The proliferation of advance technology from the west however, was responsible for the survival of other form of entertainment after the economic crisis.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: Entertainments -- Iloilo City